Hybrid core-shell nanowire electrodes utilizing vertically aligned carbon nanofiber arrays for high-performance energy storage - Klankowski, Steven Arnold (Kansas State University, 2015)
Nanostructured electrode materials for electrochemical energy storage systems have been shown to improve both rate performance and capacity retention, while allowing considerably longer cycling lifetime. The nano-architectures provide enhanced kinetics by means of larger surface area, higher porosity, better material interconnectivity, shorter diffusion lengths, and overall mechanical stability. Meanwhile, active materials that once were excluded from use due to bulk property issues are now being examined in new nanoarchitecture. Silicon was such a material, desired for its large lithium-ion storage capacity of 4,200 mAh g[superscript]-1 and low redox potential of 0.4 V vs. Li/Li[superscript]+; however, a ~300% volume expansion and increased resistivity upon lithiation limited its broader applications. In the first study, the silicon-coated vertically aligned carbon nanofiber (VACNF) array presents a unique core-shell nanowire (NW) architecture that demonstrates both good capacity and high rate performance. In follow-up, the Si-VACNFs NW electrode demonstrates enhanced power rate capabilities as it shows excellent storage capacity at high rates, attributed to the unique nanoneedle structure that high vacuum sputtering produces on the three-dimensional array. Following silicon’s success, titanium dioxide has been explored as an alternative highrate electrode material by utilizing the dual storage mechanisms of Li+ insertion and pseudocapacitance. The TiO[subscript]2-coated VACNFs shows improved electrochemical activity that delivers near theoretical capacity at larger currents due to shorter Li[superscript]+ diffusion lengths and highly effective electron transport. A unique cell is formed with the Si-coated and TiO[subscript]2-coated electrodes place counter to one another, creating the hybrid of lithium ion battery-pseudocapacitor that demonstrated both high power and high energy densities. The hybrid cell operates like a battery at lower current rates, achieving larger discharge capacity, while retaining one-third of that capacity as the current is raised by 100-fold. This showcases the VACNF arrays as a solid platform capable of assisting lithium active compounds to achieve high capacity at very high rates, comparable to modern supercapacitors. Lastly, manganese oxide is explored to demonstrate the high power rate performance that the VACNF array can provide by creating a supercapacitor that is highly effective in cycling at various high current rates, maintaining high-capacity and good cycling performance for thousands of cycles.
Keywords: Vertically aligned carbon nanofiber; Silicon; Manganese oxide; Lithium-ion batteries; Titanium oxide; Energy storage; Chemistry (0485); Energy (0791); Materials Science (0794)